2019
DOI: 10.1021/acs.jproteome.9b00242
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and Qualification of Serum Protein Biomarker Candidates for Cholangiocarcinoma Diagnosis

Abstract: Cholangiocarcinoma (CCA) is a major health problem in northeastern Thailand. The majority of CCA cases are clinically silent and difficult to detect at an early stage. Although abdominal ultrasonography (US) can detect premalignant periductal fibrosis (PDF), this method is not suitable for screening populations in remote areas. With the goal of developing a blood test for detecting CCA in the at-risk population, we carried out serum protein biomarker discovery and qualification. Label-free shotgun proteomics w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…The protein models demonstrated vital role for predicting prognosis, which including bladder cancer, esophageal squamous cell carcinoma and pancreatic ductal adenocarcinoma [25][26][27]. Abnormal expression of various protein biomarkers in cancer cells or inflammatory cells demonstrated prediction potential in cancers [21,28,29]. And a prediction model would demonstrate much better specificity and sensitivity than one biomarker.…”
Section: Discussionmentioning
confidence: 99%
“…The protein models demonstrated vital role for predicting prognosis, which including bladder cancer, esophageal squamous cell carcinoma and pancreatic ductal adenocarcinoma [25][26][27]. Abnormal expression of various protein biomarkers in cancer cells or inflammatory cells demonstrated prediction potential in cancers [21,28,29]. And a prediction model would demonstrate much better specificity and sensitivity than one biomarker.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, urine contains not only kidney and urinary tract proteins but also filtered plasma proteins originating from distal organs, including the brain (Decramer et al, 2008;An & Gao, 2015). Therefore, urine protein analysis may provide diagnostic and prognostic opportunities for both urogenital and non-renal diseases (Kaiser et al, 2004;Mischak et al, 2004;Nguyen et al, 2005;Tantipaiboonwong et al, 2005;Adachi et al, 2006;Ward et al, 2008;Zimmerli et al, 2008;Kentsis et al, 2009;Nagaraj & Mann, 2011;Kentsis et al, 2013;Metzger et al, 2013;Duangkumpha et al, 2019;Ferrari et al, 2019). Recent technical advances in fast and high-throughput sample preparation methods in conjunction with improvements in high-accuracy mass spectrometry (MS)-based proteomics have enabled characterization of the urinary proteome (Berger et al, 2015;Batth et al, 2019;Ding et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…To date, proteomics studies have been used to analyze the pattern of all proteins in a patient's sera of many types of cancer [12][13][14]. Recent results of Duangkumpha et al that studied the candidate proteins in sera of CCA patients compared to normal groups by mass spectrophotometry found statistically increasing levels of S100 calcium-binding protein A9 (S100A9) that had the potential to be used as the diagnostic biomarker of CCA patients [15]. A meta-analysis revealed that the detection of mucin 5AC (MUC5AC) in sera could be used as a powerful biomarker of CCA by providing a specificity of up to 97% and sensitivity of 63% [16][17][18].…”
Section: Introductionmentioning
confidence: 99%